THE INFLUENCE OF AUDITOR PROFESSIONALISM, COMPETENCE AND INDEPENDENCE ON AUDIT QUALITY OF SINTANG REGIONAL INSPECTORATE - Yulianti, Rani (ABDI EQUATOR, 2021)
The purpose of this study was to determine the effect of Professionalism, Competence, and Independence on Audit Quality at the Sintang Inspectorate office in West Kalimantan. This research uses primary data. The population in this study were all auditors working in the Sintang Inspectorate Office in West Kalimantan. The method used in sample selection is purposive sampling. Data collection techniques were carried out using a questionnaire with a total sample of 35 respondents. The analytical method used in this study is multiple linear regression analysis with the help of SPSS 24. The results of this study indicate that: (1) Professionalism has no significant effect on Audit Quality (2) Competence has no significant effect on Audit Quality (3) Independence no significant effect on Audit Quality.